Kombinasi Penggunaan Urin Kelinci dan Ekstrak Daun Pepaya (Carica papaya L.) terhadap Kelimpahan Hama pada Tanaman Pakcoy (Brassica rapa L.) - Devitriyani, Ida Ayu; Adnyana, I Made Mega; Yuliadhi, Ketut Ayu (Agrotrop : Journal on Agriculture Science, 2023)
Combination of Rabbit Urine and Papaya Leaf Extract (Carica Papaya L.) Usage on Pest Abundance on Pakcoy Plants (Brassica rapa L.). Pak coy (Brassica rapa L.) is a vegetable that are rich in nutrients. According to the Central Statistics Agency (2021) the production of Brasicaceae in Bali from 2018 to 2020 has been fluctuated. One of the factor’s hindering productions is the existence of pest attacks. This study aims to determine the effect of a combination of rabbit urine and papaya leaf extract on the types of pests, pest attack intensity, diversity and abundance of pests that attack pak coy plants in Penebel, Tabanan, Bali. The research held in July 2022 – November 2022 with a factorial Randomized Block Design (RBD) of 2 factors, the first factor was rabbit urine and papaya leaf extract and the second factor was concentration. Rabbit urine consisted of 4 concentrations (K0: 0 ml/l water, K1: 20 ml/l water, K2: 40 ml/l water, K3: 60 ml/l water) and papaya leaf extract consisted of 3 concentrations (P0: 0 ml/l water, P1: 400 ml/l water, P2: 600 ml/l water). The results showed that there were four types of pest species attacked pakcoy plants namely Atractomorpha crenulata (75 individuals), Oedaleus infernalis (63 individuals), Plutella xylostella (57 individuals), and the least was Vaginula bleekeri (21 individuals). The effective combinations of rabbit urine and papaya leaf extract to reduced the intensity attacks of pest was rabbit urine 60 ml/l water with papaya leaf extract 600 ml/l water (K3P2) of 7.4%, the highest damage showed by the control treatment (K0P0) of 70%. The index diversity species of pest found in all treatments was moderate. The lowest abundance of pest species was found in the K3P2 treatment (4 individuals), the highest in the K0P0 treatment (55 individuals). There was not found interaction effect between rabbit urine and papaya leaf extract.